2009
DOI: 10.3171/2009.6.spine09216
|View full text |Cite
|
Sign up to set email alerts
|

The impact of automatic retractors on the esophagus during anterior cervical surgery: an experimental in vivo study in a sheep model

Abstract: Object Postoperative dysphagia is a well-recognized complication of the anterior surgical approach to the cervical spine. However, its incidence and etiology remain unknown. The aim of this study was to investigate the impact of automatic retractor use on the esophagus and to describe the related pathological changes that might occur during cervical spine surgery. Methods A single-level cervical discecto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 33 publications
0
15
0
Order By: Relevance
“…Previous in vivo studies have demonstrated similarities between the ovine and human esophagus with respect to thickness and histological structure [3]. This led us to hypothesize that the newborn lamb is a relevant model for swallowing studies in certain neonatal conditions.…”
Section: Main Textmentioning
confidence: 87%
“…Previous in vivo studies have demonstrated similarities between the ovine and human esophagus with respect to thickness and histological structure [3]. This led us to hypothesize that the newborn lamb is a relevant model for swallowing studies in certain neonatal conditions.…”
Section: Main Textmentioning
confidence: 87%
“…72 Moreover, patients presenting after anterior cervical disk fusion procedures may complain of solid food dysphagia, presumed to be caused by pharyngeal plexus injury. 73,74 This condition may not improve with intervention and, therefore, affected patients must be counseled regarding realistic expectations. 75 …”
Section: Preoperative Considerationsmentioning
confidence: 99%
“…However, transposition of the present results from newborn lambs to human infants must be made with caution. Indeed, anatomical differences with regards to the extent of striated muscle along the esophagus (upper third only in humans vs. entire esophagus in the sheep) [28], as well as bolus propagation velocity (5 to 10 times slower in humans vs. sheep) [19], are noticeable. On the other hand, there are clear similarities between the two species, including the presence of well-determined upper and lower esophageal sphincters recorded by manometry in the lamb (personal unpublished results), the fact that the preruminant lamb is monogastric in the first week of life [29] and the presence of spontaneous gastroesophageal refluxes, with several characteristics close to the human infant [19].…”
Section: Limitations Of the Studymentioning
confidence: 99%